SOCIALIZATION OF QRIS USED TO ACCELERATE FINANCIAL TRANSACTIONS FOR SMALL MICRO ENTERPRISE - imami, Annisa; Oktavia Harahap, Annisa; Alifia Zahra, Falira; Rezeki, Mhd; Ritonga, Ritonga; Fatira AK, Marlya; Nuraini, Nuraini; Budi Prihatin, Titis (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2025)
These Community Services do socialize for small micro-enterprises to use QRIS to Facilitate Financial Transactions